2022
DOI: 10.3389/fnagi.2022.844534
|View full text |Cite
|
Sign up to set email alerts
|

A Neuron, Microglia, and Astrocyte Triple Co-culture Model to Study Alzheimer’s Disease

Abstract: Glial cells are essential to understand Alzheimer’s disease (AD) progression, given their role in neuroinflammation and neurodegeneration. There is a need for reliable and easy to manipulate models that allow studying the mechanisms behind neuron and glia communication. Currently available models such as co-cultures require complex methodologies and/or might not be affordable for all laboratories. With this in mind, we aimed to establish a straightforward in vitro setting with neurons and glial cells to study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 43 publications
2
12
0
1
Order By: Relevance
“…Luchena et al (2022) developed the triplet co-culture model of the murine rat neurons, astrocytes, and microglia. Similar to our study, the neurons in this triplet co-culture model developed longer neurite branches and expressed more post-synaptic markers, while the co-cultured astrocytes showed ramified morphology compared to the monocultured astrocytes [ 60 ]. Furthermore, microglia in the triplet co-culture model express less pro-inflammatory markers and more anti-inflammatory markers [ 60 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Luchena et al (2022) developed the triplet co-culture model of the murine rat neurons, astrocytes, and microglia. Similar to our study, the neurons in this triplet co-culture model developed longer neurite branches and expressed more post-synaptic markers, while the co-cultured astrocytes showed ramified morphology compared to the monocultured astrocytes [ 60 ]. Furthermore, microglia in the triplet co-culture model express less pro-inflammatory markers and more anti-inflammatory markers [ 60 ].…”
Section: Discussionsupporting
confidence: 81%
“…Similar to our study, the neurons in this triplet co-culture model developed longer neurite branches and expressed more post-synaptic markers, while the co-cultured astrocytes showed ramified morphology compared to the monocultured astrocytes [ 60 ]. Furthermore, microglia in the triplet co-culture model express less pro-inflammatory markers and more anti-inflammatory markers [ 60 ]. In addition, co-culture of iPSC-derived neurons and rat astrocytes accelerated the maturation of iPSC-derived neurons [ 61 ].…”
Section: Discussionsupporting
confidence: 81%
“…To investigate the indirect neuroprotective effect of nicotine, we established a co-culture system of human-derived microglia and neurons. Co-culture models are often used in the study of neurological diseases to more closely mimic the actual disease state, such as in the study of Alzheimer's disease, where Luchena Celia et al created a triple co-culture model consisting of mouse astrocytes, neurons, and microglia [49] . To investigate the effect of microglia on cortical neurons, Lopez-Lengowski Kara et al generated microglia from human induced pluripotent stem cells (iPSCs) and co-cultured them with cortical neurons [50] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that astrocytes are the most widely distributed neuroglia in the CNS. They exhibit complex interactions with neurons, and their activation mediates neuronal in ammation, which plays an important role in the development of neurodegeneration [23]. The astrocyte response to neuronal damage leads to the development of reactive astrocytes, a common feature of neurodegeneration disease, especially AD [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%